Consultation documents on services legislation for aborigines and Torres Strait Islanders in Queensland - Brennan, Frank, 1954- ([Brisbane?] : [the author?], 1982)
Effects of expected repeal of Aborigines and Torres Strait Islanders Acts, views of Aboriginal residents on administration of their communities; statements by Queensland heads of churches (21.7.81, 9.3.82, 30.3.82); statement by Aboriginal Advisory Council Working Party, 27 Aug. 1982; deeds of grant in trust legislation; history of Aboriginal reserve boundaries; land rights and self-determination; Community Services bills.
Keywords: Aboriginal Australians -- Legal status, laws, etc. -- Queensland; Torres Strait Islanders -- Queensland -- Legal status, laws, e tc; Aboriginal Australians -- Queensland -- Government relations; Torres Strait Islanders -- Queensland -- Government relations; Land rights - Excisions and leases - Land grants and leases to Aborigines; Religions - Christianity - Catholic Church; Law - Land - State and Territory - Queensland; Government policy - Self determination - 1972-1984.; Law - Administrative law - Queensland; Land rights - Excisions - Land grants and leases to Aborigines; Attitudes - Indigenous attitudes; Government policy - State and territory - Queensland; Brisbane (SE Qld SG56-15)